EDUKASI SWAMEDIKASI PENGGUNAAN OBAT ASAM URAT PADA PEMERIKSAAN KESEHATAN BERKALA - Mildawati, Ratna; Prasetyo Nugroho, Bandhi; Prasetyawan, Fendy; Kristjono, Ary; Saristiana, Yuneka (Stikes Yarsi Mataram, 2024)
Self-medication or self-medication is the use of drugs or self-soothing forms of behavior to treat a perceived or real illness. Most Indonesians practice self-medication or use drugs to cure diseases, including gout and cholesterol. Aim: To increase understanding of how to self-medicate using gout and cholesterol medication. The method used is lectures related to education through leaflets and PPTs, discussions and questions and answers. The results of the Self-Medication Education after the pretest and posttest were that of the 32 participants, 5 were in the good category, 10 were adequate and 17 were poor, to 28 were good and 4 were sufficient, so that in this activity it can be concluded that there is an understanding of the community to carry out self-medication for gout and the importance of carrying out regular examinations so that they can detect early if there is an increase in uric acid